2022
DOI: 10.1021/acs.cgd.2c00150
|View full text |Cite
|
Sign up to set email alerts
|

Supramolecular Synthon Promiscuity in Phosphoric Acid–Dihydrogen Phosphate Ionic Cocrystals

Abstract: Approximately 80% of active pharmaceutical ingredients (APIs) studied as lead candidates in drug development exhibit low aqueous solubility, which typically results in such APIs being poorly absorbed and exhibiting low bioavailability. Salts of ionizable APIs and, more recently, pharmaceutical cocrystals can address low solubility and other relevant physicochemical properties. Pharmaceutical cocrystals are amenable to design through crystal engineering because supramolecular synthons, especially those sustaine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
11
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 81 publications
0
11
0
Order By: Relevance
“…71,72 HES belongs to the group of natural products known as flavonoids and contains multiple phenolic groups. Phenols are classified as medium strength H-bond donors 38 and have been established as being able to form supramolecular heterosynthons with Hbond acceptors such as chloride anions, 39 carboxylate moieties, 40 and aromatic nitrogen bases. 41 Recently, we reported a crystal engineering study on ICCs of phenol and substituted phenol derivatives with their conjugate bases, which indicated that the phenol…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…71,72 HES belongs to the group of natural products known as flavonoids and contains multiple phenolic groups. Phenols are classified as medium strength H-bond donors 38 and have been established as being able to form supramolecular heterosynthons with Hbond acceptors such as chloride anions, 39 carboxylate moieties, 40 and aromatic nitrogen bases. 41 Recently, we reported a crystal engineering study on ICCs of phenol and substituted phenol derivatives with their conjugate bases, which indicated that the phenol…”
mentioning
confidence: 99%
“…Whereas cocrystals have long been known, their amenability to design through crystal engineering approaches was not well recognized until the early 2000s when four papers detailed the design of pharmaceutical cocrystals. Successful crystal engineering approaches to cocrystal design are generally based on a knowledge of possible H-bonded supramolecular synthons . In this context, H-bonded supramolecular heterosynthons between coformers are key to understanding and designing cocrystals since their hierarchies can be used to project whether a cocrystal is amenable to being readily isolated . Pharmaceutical cocrystals can significantly diversify the number of crystal forms available for a given API, thereby improving the likelihood that a crystalline form suitable for use in a drug product will be identified.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The information on self-assemblies with enhanced composition becomes important on applications in materials, or for recovery from solution where they may remain as vulnerable contaminants. 31 Appropriately functionalized acid or base derivatives form salts or ionic cocrystals [32][33][34][35][36][37] or stabilize zwitterion forms. 38 The stacking effect and the concomitant hydrogen bond donor/acceptor behavior of naphthalimide derivatives make them attractive to generate polymorphs.…”
Section: Introductionmentioning
confidence: 99%
“…17,18 By introducing three different components (rather than two as in salts), ionic co-crystals increase diversity and create new sets of materials and properties to explore, like it was recently reported for phosphoric acid–dihydrogen phosphate co-crystals. 19…”
Section: Introductionmentioning
confidence: 99%